A refined protocol for calculating MNI in archaeological molluscan shell assemblages: a Marshall Islands case study. (May 2015) - Harris, Matthew; Weisler, Marshall; Faulkner, Patrick
Abstract: Comprehensive and transparent protocols for calculating Minimum Number of Individuals (MNI) for archaeological faunal assemblages are critical to data quality, comparability, and replicability. MNI values for archaeological molluscan assemblages are routinely calculated by counting a select range of Non-Repetitive Elements (NREs). Most commonly, only the frequency of the spire of gastropods and the umbo or hinge of bivalves are recorded. Calculating MNI based only on the frequency of these NREs can underestimate the relative abundance of particular molluscan shell forms. Using archaeological mollusc assemblages from two sites in the Marshall Islands as a case study, we outline a new protocol (tMNI) that incorporates a wider range of NRE and calculates MNI based on the most frequently occurring NRE for each taxon. The principles that underlie the tMNI method can be modified to be regionally or assemblage specific, rather than being a universally applicable range of NRE for the calculation of MNI. For the Marshall Islands assemblages, the inclusion of additional NRE in quantification measures led to (1) a 167% increase in relative abundance of gastropods and 3% increase in bivalves (2) changes to rank order abundance, and (3) alterations to measures of taxonomic richness and evenness. Given these results for the Marshall Islands assemblages, tMNI provides more accurate taxonomic abundance measures for these and other archaeological molluscan assemblages with similar taxa. These results have implications for the quality of zooarchaeological data increasingly utilised by conservation biologists, historical ecologists and policy makers. Highlights: Molluscan MNI values are routinely calculated using a restricted range of Non-Repetitive Elements (NREs). A new protocol is described that expands the range of NREs for MNI calculation. The new protocol for calculating MNI increased abundance of gastropods by 167%. Richness and evenness measures, as well as rank order were markedly influenced by quantification protocol.